Influence of Person-Organization Fit and Servant Leadership on Innovative Work Behavior: Psychological Empowerment as a Mediating Variable - suraya, Nana; suryosukmono, gerry (Student Journal of Business and Management, 2024)
This study aims to examine the effect of person-organization fit, servant leadership on innovative work behavior mediated by psychological empowerment. This research method is quantitative, and primary data is collected by means of a hand delivery survey to employees of the Bengkulu Province Public Works and Spatial Planning Office. The number of samples in this study were 258 respondents. However, the number of questionnaires that can be processed is 154. The data is processed using PLS SEM (Partial Least Square). The results obtained in this study: (1) person-organization fit has a significant negative effect on innovative work behavior (2) servant leadership has a significant positive effect on innovative work behavior (3) psychological empowerment has a significant positive effect on innovative work behavior (4) person- organization fit has a significant positive effect on psychological empowerment (5) servant leadership has a significant positive effect on psychological empowerment (6) psychological empowerment mediates the effect of person-organization fit on innovative work behavior (7) psychological empowerment mediates the influence of servant leadership on innovative work behavior